Kemandirian Fiskal dan Ketergantungan Transfer Pusat: Analisis Laporan Realisasi Anggaran Pemerintah Kota Ambon Tahun 2018–2024 - Alend Talla; Franco Benony Limba; Shella Gilby Sapulette (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the level of fiscal independence and dependence on central government transfers in the Ambon City Government during the 2019–2024 period. The research employs a descriptive quantitative approach using secondary data from the Budget Realization Reports (LRA). The analysis is conducted through the calculation of fiscal independence ratios, transfer dependency ratios, as well as trend and annual growth analysis. The results indicate that the level of fiscal independence in Ambon City remains low and fluctuates, with a relatively small contribution of Local Own-Source Revenue (PAD) to total revenue. In contrast, the level of dependence on central government transfers is high and relatively stable, indicating the dominance of transfer funds in the regional revenue structure. These findings suggest that the region’s fiscal capacity is still weak and fiscal independence has not been optimally achieved. Therefore, strategic efforts are needed to enhance local revenue and to allocate transfer funds toward productive expenditures in order to strengthen the regional fiscal structure.